2019
DOI: 10.1055/s-0039-1692189
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study Using the String of Pearls Tibial Plateau Levelling Osteotomy Locking Plate for the Treatment of Cranial Cruciate Ligament Disease

Abstract: Objective The aim of this study was to describe the use of String of Pearls (SOP) tibial plateau levelling osteotomy (TPLO) locking plates for the treatment of cranial cruciate ligament disease and retrospectively assess osteotomy healing, tibial plateau angle (TPA) change (c) and overall complication rates. Methods Medical records and radiographic studies of 170 SOP TPLO surgical procedures were analysed. Radiographic measurement of TPAc and osteotomy union was determined 6 to 8 weeks postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Use of smaller screws in non-locking function has been reported as a means of improving plateto-bone contact with SOP screws, but the smaller screw is usually subsequently removed and replaced with a standard sized locking screw. 35 Surgical records in this case did not reveal a specific reason for maintenance of the 2.0 mm nonlocking screw. Screw loosening associated with SOP plates has previously been documented in a clinical study reporting use of this implant for stabilization of tibial plateau levelling osteotomy with an incidence of 4/170 cases 35 and as a mode of failure in a cadaveric mechanical study of this implant, 36 and it has been suggested that this may be associated with micromotion occurring between the plate and the screw.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Use of smaller screws in non-locking function has been reported as a means of improving plateto-bone contact with SOP screws, but the smaller screw is usually subsequently removed and replaced with a standard sized locking screw. 35 Surgical records in this case did not reveal a specific reason for maintenance of the 2.0 mm nonlocking screw. Screw loosening associated with SOP plates has previously been documented in a clinical study reporting use of this implant for stabilization of tibial plateau levelling osteotomy with an incidence of 4/170 cases 35 and as a mode of failure in a cadaveric mechanical study of this implant, 36 and it has been suggested that this may be associated with micromotion occurring between the plate and the screw.…”
Section: Discussionmentioning
confidence: 64%
“…35 Surgical records in this case did not reveal a specific reason for maintenance of the 2.0 mm nonlocking screw. Screw loosening associated with SOP plates has previously been documented in a clinical study reporting use of this implant for stabilization of tibial plateau levelling osteotomy with an incidence of 4/170 cases 35 and as a mode of failure in a cadaveric mechanical study of this implant, 36 and it has been suggested that this may be associated with micromotion occurring between the plate and the screw. 37 It was interesting that screw loosening occurred in the caudal (ischial) fracture segment in both cases with loose screws in our study, and we speculate that bone quality in this area may predispose to higher micromotion by comparison with screws placed dorsal or cranial to the acetabulum.…”
Section: Discussionmentioning
confidence: 64%
“…In several studies, other potential sources of bias have been identified ( Table 1 ). Many studies were of retrospective nature ( 42 , 50 , 52 , 53 , 55 , 56 , 58 61 , 63 , 64 , 71 95 ) which imposes a high risk of bias as protocols have not been standardized beforehand. Also, reported outcomes which might be different from the true outcome as potential follow-up losses cannot be identified.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study of the SOP TPLO system, which uses only locked screws, showed increased rock back and decreased radiographic healing scores, compared to other TPLO plates which include DC holes. 7 11 12 This may suggest that compression at the osteotomy is beneficial for the construct.…”
Section: Discussionmentioning
confidence: 99%